20. Fluoroquinolone and Overall Outpatient Antibiotic Prescribing Trends in Adults, 2011 to 2018. (31st December 2020) - Gouin, Katryna A; King, Laura M; Bartoces, Monina; Roberts, Sarah Kabbani; Rebecca M; Tsay, Sharon; Hicks, Lauri
Abstract: Background: Fluoroquinolones (FQs) are the third most commonly prescribed antibiotics among U.S. outpatients, and the second most commonly prescribed class among adults ≥ 65 years of age. However, FQ use has been associated with severe adverse events, especially among older adults. As a result, in 2016 the U.S. Food and Drug Administration (FDA) issued warnings against FQ use when other agents may be effective. We assessed changes in outpatient FQ prescribing relative to overall antibiotic prescribing from 2011 to 2018. Methods: We estimated annual antibiotic prescription rates in adults ≥ 20 years of age for all classes and FQs using national prescription dispensing count data from IQVIA Xponent (numerator) and census estimates (denominator) for 2011 to 2018. We used Poisson models to estimate prevalence rate ratios (PRR) and 95% confidence intervals (CIs) comparing antibiotic prescription rates overall and stratified by age group from 2011 to 2018. The Chi-square test was used to compare the percent decrease in rates between age groups. Results: From 2011 to 2018, prescription rates in adults for all antibiotics decreased by 2% (PRR 0.98, 95% CI: 0.98-0.98); FQ prescription rates decreased by 30% (PRR 0.70, 95% CI: 0.69–0.70), with the largest decline from 2015–2018 (Figure 1). Adults ≥ 65 years had the highest FQ prescription rates for 2011 to 2018, at a rate 2.37 (95% CI: 2.32, 2.42) times that of adults 20–64 years (Figure 2). The FQ prescribing rate in adults 20–64 experienced a greater decrease from 2011 to 2018 than the rate in adults ≥ 65 years (p< 0.0001), with a 35% decrease (PRR 0.65, 95% CI: 0.65, 0.65) in adults 20–64 years compared to a 29% (PRR 0.71, 95% CI: 0.71-0.71) decrease in adults ≥ 65 years (Figure 2). Decreases in total outpatient antibiotic and fluoroquinolone prescribing rates among adults in the United States from 2011 to 2018 Decreases in outpatient fluoroquinolone prescriptions per 1, 000 persons by age group in the United States from 2011 to 2018 Conclusion: FQ prescribing decreased markedly compared to overall antibiotic prescribing from 2011 to 2018, which was likely due in part to FDA warnings on FQ-associated adverse events. However, FQ prescribing among older adults remained high during this period and did not decrease as much as in younger adults. Further evaluation of the diagnoses associated with prescribing may provide additional opportunities to optimize FQ prescribing practices, especially among older adults. Disclosures: All Authors : No reported disclosures